Pengaruh Kemampuan dan Motivasi Terhadap Kinerja Pegawai Kantor Pelayanan Terpadu (Studi Pada Kantor Pelayanan Terpadu Lumajang) - Shafiah, Septiani Agustina (Jurnal Administrasi Publik, 2014)
Abstract: Influence of the ability and motivation of employee performance in Integrated Services Office (Case Studies in Integrated Services Office of Lumajang Regency). The purpose of this study was to determine the effect on employee performance capabilities, the influence of motivation on employed performance, and the influence of ability and motivation on employee performance the staff of the Integrated Services of Lumajang Regency.  Based on the calculation results of multiple linear regression analysis that has been done showing the ability of the model to explain the influence of independent variables on the dependent variable is large, it can be seen in the value of Adj. R. Square (R2) is equal to 0.714. The results of the F test and t-test can be seen that the partial and concurrent variable abilities and motivation, the result is a significant effect on performance the staff of the Integrated Services of Lumajang Regency (Kantor Pelayanan Terpadu Kabupaten Lumajang). Based on the results of the regression coefficient (b) each motivation variable has dominant effect on the performance of the staff  in the Integrated Services of Lumajang. That is because the regression coefficient (Standardized Coenffucients Beta) Based on motivation variable has the greatest value when compared with variable capability that is equal to 74.1%.   Keywords: The ability, Motivation and Employee Performance. Abstrak: Pengaruh Kemampuan Dan Motivasi Terhadap Kinerja Pegawai Kantor Pelayanan Terpadu (Studi Pada Kantor Pelayanan Terpadu Lumajang). Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kemampuan terhadap kinerja pegawai, pengaruh motivasi terhadap kinerja pegawai, dan pengaruh kemampuan dan motivasi terhadap Kinerja Pegawai Kantor Pelayanan Terpadu. Berdasarkan hasil perhitungan analisis regresi linier berganda yang telah dilakukan menunjukkan kemampuan model dalam menjelaskan pengaruh variabel independent terhadap variabel dependent adalah besar, hal tersebut dapat dilihat pada nilai Adj. R. Square (R2) yaitu sebesar 0,714. Hasil uji F dan uji t dapat diketahui bahwa secara parsial dan simultan variabel kemampuan dan motivasi, berpengaruh signifikan terhadap kinerja pegawai Kantor Pelayanan Terpadu Lumajang. Berdasarkan hasil koefisien regresi (b) masing-masing variabel motivasi mempunyai pengaruh dominan terhadap kinerja pegawai Kantor Pelayanan Terpadu Lumajang. Hal tersebut dikarenakan koefisien regresi (Standardized Coeffucients Beta) pada variabel motivasi mempunyai nilai terbesar jika dibandingkan dengan variabel kemampuan yaitu sebesar 74,1%.   Kata Kunci : Kemampuan, Motivasi dan Kinerja Pegawai